Implementation of Article 33 Paragraphs 2 and 3 of the 1945 Constitution in Granting Concessions for Natural Resource Management to Foreign Companies from International Private Law Perspective: A Case Study of PT XYZ - R. Gatot Prio Utomo; Heliaantoro, Heliaantoro (Greenation Research & Yayasan Global Resarch National, 2024)
The Indonesian Constitution of 1945, particularly Article 33 paragraphs 2 and 3, establishes the fundamental principles governing the management of the nation's natural resources. These clauses stipulate that the state controls and utilizes natural resources for the maximum benefit of the people. However, the implementation of these constitutional principles in practice, especially in the context of granting concessions to foreign companies, raises complex legal and policy challenges. This research paper examines the implementation of Article 33 in the case of PT XYZ Indonesia, a foreign mining company operating in Indonesia, from the perspective of international private law. The study analyses the legal and regulatory frameworks governing the management of natural resources, the mechanisms for granting concessions to foreign companies, and the implications for the welfare of the Indonesian people. The findings shed light on the delicate balance between upholding the state's sovereignty over natural resources and attracting foreign investment and the role of international private law in shaping this dynamic.